2021
DOI: 10.1590/1806-9282.20210232
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obstructive sleep apnea syndrome and functional capacity in patients with diabetes mellitus type 2: an observational transversal study

Abstract: OBJECTIVE:The aim of this study was to verify the association among obstructive sleep apnea, functional capacity, and metabolic control. METHODS: This was a cross-sectional study involving individuals of both sexes with clinical diagnosis of diabetes mellitus type 2 who were above 18 years of age. The assessment consisted of a volunteer identification form, a 2-minute step test, and the Stop-Bang questionnaire. In order to assess metabolic control, HbA1c and fasting glucose data were collected from medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…This result was consistent with findings from a study done in Nigeria and Jordan using the Berlin questionnaire, which showed that the prevalence of high risk of OSA was 27% and 31%, respectively ( 11 , 31 ). However, the results of this study were higher than those conducted in Benin, Brazil, and Saudi Arabia using SBQ, which reported that the prevalence of high risk of OSA was 14.1%, 17%, and 15.2%, respectively ( 4 , 9 , 32 ). This variation might be due to differences in the study population and sample size, which was smaller in the studies done in Brazil and Saudi Arabia but larger in the Benin study.…”
Section: Discussioncontrasting
confidence: 88%
“…This result was consistent with findings from a study done in Nigeria and Jordan using the Berlin questionnaire, which showed that the prevalence of high risk of OSA was 27% and 31%, respectively ( 11 , 31 ). However, the results of this study were higher than those conducted in Benin, Brazil, and Saudi Arabia using SBQ, which reported that the prevalence of high risk of OSA was 14.1%, 17%, and 15.2%, respectively ( 4 , 9 , 32 ). This variation might be due to differences in the study population and sample size, which was smaller in the studies done in Brazil and Saudi Arabia but larger in the Benin study.…”
Section: Discussioncontrasting
confidence: 88%
“…The total score is the sum of 8 questions with a score range of 0-24. Scores greater than ten are associated with mild to moderate OSA [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…AHI is defined as the sum of sleep apnea and hypopnea divided by the hours of sleep. There are three types of OSA degrees based on the America American Academy of Sleep Medicine, namely: a) mild OSA (AHI score 5-15); b) Moderate OSA (AHI score [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]; and c) severe OSA (AHI value of more than 30).…”
Section: Literature Reviewmentioning
confidence: 99%